A rare cationic building block that generates a new type of polyhedral network with "cross-linked" pto topology. Issue 22 (23rd February 2016) - Lusi, Matteo; Fechine, Pierre B. A.; Chen, Kai-Jie; Perry, John J.; Zaworotko, Michael J.
Abstract : A rare copper-based MBB enables the generation of a novel high symmetry porous metal–organic material exhibiting a hitherto unreported 3, 5-c topology. Abstract : A rare 8-connected cationic building block, [Cu2 L8 (μ-MF6 )] 2+ (L = pyridyl ligand, M = Si, Ti, Ge, Zr or Sn), enables the formation of a small cubicuboctahedral supramolecular building block, SBB, when complexed by 2, 4, 6-tris(4-pyridyl)pyridine. The coordination network resulting from fusing the square faces of the SBBs can be described as apto topology in which half of the square faces are cross-linked by MF6 2− moieties, and represents the first example of a new 3, 5-c topology.